STRATEGIC FORESIGHT AND ADAPTIVE DECISION MAKING IN MSMES: A CAPABILITY-BASED FRAMEWORK - Farida Yulianty; Arif Budi Raharja (Journal of Jabar Economic Society Networking Forum, 2025)
This conceptual paper develops an integrative framework for strategic foresight and adaptive decision making in micro, small, and medium enterprises (MSMEs). It synthesizes established literature on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial ecosystems. The analysis explains how environmental scanning, scenario thinking, decision discipline, resource reconfiguration, and organizational learning can be organized into proportionate managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The framework proposes diagnosis, capability mapping, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention as a cumulative cycle. Implications are developed for owner-managers, support institutions, and future empirical research.